ANALISA PENGARUH VARIABILITAS IKLIM TERHADAP KASUS KEJADIAN DEMAM BERDARAH DENGAN MENGGUNAKAN PENDEKATAN MODEL REGRESI: STUDI KASUS KOTA BANDUNG - Joyodiningrat, M. Henry; Kurniawan, Yonatan (Creative Research Journal, 2024)
Dengue fever (DHF) is a disease transmitted by mosquito vectors that becomes a worldwide problem every year. Bandung City as the capital city of West Java Province is a vulnerable area for DHF as seen from the high number of cases and deaths due to DHF. Climate variability such as temperature, rainfall, humidity and wind speed, has an influence on the incidence of DHF which affects the life cycle of mosquitoes, breeding media, and also the reach of mosquitoes to humans. The high number of cases will affect the sustainability of regional development, one of which has implications for the high burden on the health budget. Based on the regression model, there is a relationship between climate variability and health outcomes. Climate variability simultaneously affects the incidence of dengue fever in Bandung City. With R2 value of 0.737. The proven influence of climate variability on dengue disease rates in Bandung City can be used in developing an early warning system to prevent and reduce the number of cases in the form of more accurate disease prevention activities before the number of cases increases.